Never again. Once used for cardiac catherization the radial artery cannot be used for CABG. Issue 12 (1st October 2021) - Chadow, David; Soletti, Giovanni J.; Gaudino, Mario
Abstract: The use of the radial artery (RA) as a conduit in coronary artery bypass grafting (CABG) has been steadily increasing since the early 1990s and based on the most recent data may well become the standard of care for patients with multivessel coronary artery disease requiring multiple arterial grafts. The transradial access (TRA) approach for cardiac catherization has also increased steadily in use by interventional cardiologists owing to its reduction in bleeding and vascular complications when compared with the femoral approach and is now considered the preferred arterial access. However, prior use of TRA for cardiac catherization is a contraindication for the use of the RA for CABG because of high rates of structural damage to the vascular wall and potential for graft failure. In this issue of the Journal of Cardiac Surgery Clarke et al. examine the RA of two patients who had TRA for coronary angiography 8 and 12 years prior and note that both patients had chronic injury with dissection and obstruction of the lumen secondary to fibrosis suggesting that TRA causes long‐term and irreversible damage rendering them unsuitable as conduits for CABG.